Sequestration of carbon dioxide from fossil fuel production and use an overview of rationale, techniques and implications - Johnston, Paul; Santillo, David; Stringer, Ruth; Parmentier, Rémi; Hare, Bill; Krueger, Martina (Environmental science and pollution research international, 1999)
Nations around the globe agreed to significant reductions in greenhouse gas emissions when they signed the Kyoto Protocol. Although the Kyoto Protocol largely sought reductions in source emissions of problematic compounds, many questions remain regarding the ability of national governments to realistically achieve their target emission reductions. As a result, several techniques for increasing carbon sequestration have been theorized. The advantages and drawbacks of CO sub(2) sequestration in the world's oceans are detailed, including supplying limiting nutrients to vast areas of the oceans to boost primary production, the direct disposal of CO sub(2) to seawater, and the injection of excess CO sub(2) to sub-seabed geological formations.